Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Tune into Yes 13 : A Benefit Concert & Silent Auction - Youth Employment Services (YES) (2019)
Featuring an impressive silent auction, complimentary food, wine, beer and live entertainment, Tune In To YES is not only an exciting networking and social event, it is also an opportunity to help job-seekers, entrepreneurs and artists in our community.

Program Book for Winter/Spring 2017 - Youth Employment Services (YES) (2017)
issued: January, 2017/August, 2017

Program Book for Winter/Spring 2016 - Youth Employment Services (YES) (2016)
issued: January, 2016/August, 2016

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)
issued: January, 2018/August, 2018

Program Book - Youth Employment Services (YES) (2013)
issued: Winter, 2013/Spring, 2013

The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

Helping Montreal's Youth into the Workforce - Youth Employment Services (YES) (2011)

Who We Are - Youth Employment Services (YES) (2020)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

YES Montreal Helps Entreprenuers Capitalize on Opportunities at the 13th Annual Entrepreneurship Conference : Made in Montreal - Youth Employment Services (YES) (2010)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)
Number of pages: 1

YES E-News Monthly - Youth Employment Services (YES)
Number of pages: 1

YES E-News : September 2007 - Youth Employment Services (YES) (2007)
Number of pages: 1

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)
Number of pages: 4

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)
Number of pages: 2

Making your Job Search Work for You - Youth Employment Services (YES)